Molecular Mechanism of the Antiproliferative Activity of Short Immunostimulating dsRNA - Zharkov, Mikhail I.; Zenkova, Marina A.; Vlassov, Valentin V.; Chernolovskaya, Elena L. (Frontiers in Oncology, 2019)
Small double-stranded RNAs with certain sequence motifs are able to interact with pattern-recognition receptors and activate the innate immune system. Recently, we identified a set of short double-stranded 19-bp RNA molecules with 3-nucleotide 3’-overhangs that exhibited pronounced antiproliferative activity against cancer cells in vitro, and antitumor and antimetastatic activities in mouse models in vivo. The main objectives of this study were to identify the pattern recognition receptors that mediate the antiproliferative action of immunostimulating RNA (isRNA). Two cell lines, epidermoid carcinoma KB-3-1 cells and lung cancer A549 cells, were used in the study. These lines respond to the action of isRNA by a decrease in the growth rate, and in the case of A549 cells, also by a secretion of IL-6. Two sets of cell lines with selectively silenced genes encoding potential sensors and signal transducers of isRNA action were obtained on the basis of KB-3-1 and A549 cells. It was found that the selective silencing of PKR and RIG-I genes blocked the antiproliferative effect of isRNA, both in KB-3-1 and A549 cells, whereas the expression of MDA5 and IRF3 was not required for the antiproliferative action of isRNA. It was shown that, along with PKR and RIG-I genes, the expression of IRF3 also plays a role in isRNA mediated IL-6 synthesis in A549 cells. Thus, PKR and RIG-I sensors play a major role in the anti-proliferative signaling triggered by isRNA.